Disodium Cantharidinate and Vitamin B6 Injection Adjunct with Platinum-Based Chemotherapy for the Treatment of Advanced Non-Small-Cell Lung Cancer: A Meta-Analysis. (12th March 2019) - Wang, Zhichao; Feng, Fanchao; Wu, Qi; Jin, Yihan; Gu, Cheng; Xu, Yong; Zhou, Xianmei; He, Hailang
Abstract : Purpose . Disodium cantharidinate and vitamin B6 (DCVB6) injection is effective and widely used for the clinical treatment of non-small-cell lung cancer (NSCLC). This meta-analysis aimed to provide evidence-based medical data for clinical treatment with DCVB6 injection. Methods . We searched 7 medical databases up to January 2018 for all randomized controlled trials (RCTs) based on DCVB6 injection combined with chemotherapy in patients with NSCLC. A manual search in relevant journals and of relevant literature on other websites was also performed. Data extraction and quality assessment were conducted independently by two reviewers. Subsequently, a meta-analysis was conducted using RevMan 5.3 software. Pooled risk ratio (RR) with 95% confidence interval (CI) was used to evaluate dichotomous and continuous outcomes, respectively. The PROSPERO ID was CRD42018086377. Results . A total of 19 RCTs were included. The results of the meta-analysis indicated that the DCVB6 injection combined with chemotherapy was superior to chemotherapy alone regarding objective response rate (RR=1.58, 95% CI 1.40-1.79), Karnofsky performance score (RR=1.68, 95% CI 1.42-1.99), clinical symptom (RR=1.68, 95% CI 1.44-1.96), white blood cell toxicity (RR=0.36, 95% CI 0.27-0.49), platelet toxicity (RR=0.46, 95% CI 0.33-0.63), and vomiting (RR=0.50, 95% CI 0.37-0.67). Conclusions . The current evidence suggests that DCVB6 injection combined with chemotherapy could increase objective response rate and Karnofsky performance score, improve clinical symptoms, and reduce side effects caused by chemotherapy in patients with NSCLC. However, these results should be carefully interpreted due to the low-quality methodology and the small sample sizes of the trials, and our conclusions should be verified by high-quality, large-scale, double-blinded RCTs.